Literature Study on Learning Physics with Problem-based Learning (PBL) Models to Improve Students' Problem-Solving Skills (Universitas Negeri Surabaya, 2023)
Problem-solving skills must be possessed by students to find solutions or get answers to problems to be solved by methods based on their understanding, especially in the field of physics. One alternative that can be used to improve problem-solving skills is with problem-Based Learning (PBL) models. This study aims to compare the implementation of learning using Problem-Based Learning models as well as knowing the effect of learning with Problem-Based Learning models on problem-solving skills. The research method is expost facto. Data collection was carried out using techniques of library research and several five related articles were obtained after going through data reduction, namely between 2018 until 2022. The existing data was analysed using qualitative and quantitative descriptive analysis. The results showed that there was a relationship between the PBL model and the problem-solving skills of the experimental class and the control class. This is indicated by the results of the experimental class being higher than the control class in the value results from the pre-test and post-test, improvement of problem-solving skills, as well as improvement per indicator of problem-solving skills. The value of problem-solving skills is in the moderate category for the experimental class and the control class is in the low category. Based on the data obtained, it can be concluded that the results of the PBL model have a higher value than the conventional model and the PBL model can improve students' problem-solving skills. Keyword: Problem-Solving Skills, Problem-Based Learning, Physics